SPECIFICITY OF AIRWAY MANAGEMENT IN THORACIC ANESTHESIA - Nikolić, Aleksandar (Acta medicae Medianae, 2022)
Until anesthesia techniques advanced in the mid-1930s, chest operations were short and difficult. Anesthesia during thoracic surgery is in itself very demanding and complicated to work with and represents a real challenge for the anesthesiologist. In order to perform the operation smoothly in patients whose respiratory reserve has already been reduced, it is necessary to exclude the lung that is being operated on and to isolate the lung that is ventilated during the surgical intervention. Double lumen tubes and endobronchial blockers are used to secure the airway and to achieve collapse and unilateral ventilation. Fiberoptic bronchoscopy is the gold standard in the world of modern thoracic anesthesia for checking the position of a double lumen tube and endobronchial blocker.airway, thoracic anesthesia, double lumen tubes, endobronchial blockers
Keywords: airway, thoracic anesthesia, double lumen tubes, endobronchial blockers